20th anniversary of axial capacitively coupled contactless conductivity detection in capillary electrophoresis - Kubáň, Pavel; Hauser, Peter C. (TrAC, Trends in analytical chemistry (Regular ed.), 2018)
Capacitively coupled contactless conductivity detection in its axial electrode arrangement was introduced to capillary electrophoresis 20 years ago. The method has since seen a strong development and has been accepted as a useful tool for the detection of inorganic as well as organic ions not only in electrophoresis but also in other analytical techniques. On this anniversary an overview of the developments is given. It can serve as an introduction for readers not familiar with the field, but it may also fill out details for readers already acquainted with contactless conductivity detection. Historical and fundamental aspects are covered as well as technical developments. Its uses in the different modes of capillary electrophoresis are discussed as are applications outside electrophoresis. •Axial C4D was introduced to CE 20 years ago.•C4D is a universal detection technique for inorganic, organic and biochemical ions.•Theoretical principles, instrumental developments and typical applications are reviewed.•C4D maturity is demonstrated by ∼1200 publications and commercialization of the device.•Use of C4D in other separation and non-separation analytical techniques is possible.